The Oxford handbook of economic inequality - Salverda, Wiemer; Nolan, Brian, 1953-; Smeeding, Timothy M. (Oxford : Oxford University Press, 2011)
Comprehensive analysis of economic inequality in developed countries. The contributors give their view on the state-of-the-art scientific research in their fields and add their own visions of future research.
Originally published: 2009.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Income distribution; Social stratification; Wealth